Pengaruh Penggunaan Zat Admixture “X” Terhadap Peningkatan Kuat Tekan Beton (Studi Kasus “Pasir Cepu dan Kerikil Rembang”) - bryan ramadhan ramadhan; Yunita Perdanawati; David Widanto; Budi Setiyadi (Universitas Katolik Soegijapranata Semarang, 2018)
This research uses Cepu sand fine aggregate as the main material of making of concrete. Cepu sand has high mud and calcium content compared to Muntilan sand.In order for Cepu sand to be used as a concrete material, it is necessary to add an integral waterproofing admixture with plasticizer content to help the aggregate density. This study, varied admixture with 0%, 50%, 100%, 150%, 200% (20ml per 1kg cement) composition. All test objects totaling 80 pieces are used for compressive strength testing with the size of 15 × 15 × 15 cm test specimens.The result of laboratory test showed that Cepu sand concrete without addition of admixture with 14 days drying was found to be the average of compressive strength of 290 kg / cm2, while the highest was obtained by addition of 100% integral waterproofing admixture with an average value of 392 kg / cm2. While on 28 days drying, the average compressive strength value is 352 kg / cm2 without using integral waterproofing admixture, while the highest is obtained with addition of 100% integral waterproofing admixture with average value of 509 kg / cm2. With additional admixture the Cepu sand has increased the compressive strength higher than Muntilan sand concrete.